Homogeneous liposome lysis assay for determination of anti-streptolysin O antibody titer in serum. - Umeda, M (1988)
We developed a liposome lysis assay for determining anti-streptolysin O antibodies (ASO) in human sera involving the use of carboxyfluorescein-entrapped multilamellar liposomes. This assay system was based on the inhibition of streptolysin O-induced liposome lysis by ASO. Briefly, after incubation of a given amount of streptolysin O with ASO for 30 min at 37 degrees C, carboxyfluorescein-entrapped liposomes composed of egg yolk phosphatidylcholine and cholesterol in a molar ratio of 1:1 were added to the mixture to determine the residual streptolysin O activity. Liposome lysis, detected as carboxyfluorescein release from the liposomes, was inversely proportional to the ASO titer. The results of within-run and between-run precision studies indicated that the liposome lysis assay is accurate and gives reproducible data. Bilirubin, hemoglobin, and triglycerides did not interfere with the liposome lysis assay. The ASO titers of 100 patient sera, evaluated by our new method and the Rantz-Randall method, showed good correlation.